A hydrophilic low surface energy modified polyether sulfone membrane and its preparation and application

CN117547980BActive Publication Date: 2026-10-27SICHUAN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311513725.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-14
Publication Date
2026-10-27
Estimated Expiration
2043-11-14

AI Technical Summary

Technical Problem

而且由于ECMO膜是在气-液界面下工作,不当的亲水性改性可能会导致液体的渗漏

Benefits of technology

[0017]本发明在ECMO中引入“亲水-低表面能”机制,如利用亲水性物质单宁酸接枝PEI,形成一层亲水基底,保证污物抵御性能;然后通过氨基和环氧基团的开环反应接枝含有短链氟的小分子,引入低表面能部分,保证污物释放性能;同时所得改性PES膜表现出优异的血液相容性;因此其能够用作ECMO中膜式氧合器,所得改性膜在模拟ECMO测试中,表现出优异的气体交换性能和抗血浆渗漏性能。此外,本发明改性膜的制备方法简单,适用范围广,具有较大的应用潜力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117547980B_ABST
    Figure CN117547980B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of modified polyether sulfone membrane of hydrophilic low surface energy and its preparation and application, belong to membrane material field.The present application provides a kind of preparation method of modified polyether sulfone membrane of hydrophilic low surface energy, the preparation method is as follows: first, polyether sulfone membrane is modified to have the polyether sulfone membrane of hydrophilic coating layer;Then the polyether sulfone membrane with hydrophilic coating layer is modified to obtain the modified polyether sulfone membrane, wherein, 3-perfluorobutyl-1,2-epoxy propane is used to carry out hydrophobic modification.The present application prepares a kind of hydrophilic low surface energy antifouling membrane, and the modified membrane obtained has excellent blood compatibility, ensures the stability under long time operation;Therefore, it is used as gas separation in ECMO, and in simulated ECMO experiment, the result proves that the modified polyether sulfone membrane obtained shows excellent oxygenation efficiency and carbon dioxide removal efficiency, and there is no plasma leakage phenomenon.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a hydrophilic, low surface energy modified polyethersulfone membrane, its preparation and application, and belongs to the field of membrane materials. Background Technology

[0002] Since the outbreak of the novel coronavirus in 2019, extracorporeal membrane oxygenation (ECMO) has received immense attention. It can temporarily replace a patient's cardiopulmonary function and is hailed as a life-saving device. The most crucial component of an ECMO device is the membrane oxygenator, also known as an artificial lung. However, ECMO equipment is expensive, costing hundreds of thousands of yuan just to set up. The most critical factor limiting ECMO prices and technology is the membrane oxygenator material. Currently, PMP material is widely used, but its blood compatibility remains a significant issue. During use, it is highly prone to protein adsorption, which not only contaminates the membrane and affects gas exchange efficiency, but also causes protein denaturation, leading to a series of adverse reactions and even inducing coagulation. This is why the application cycle of commercially available ECMO materials is generally only two weeks.

[0003] Currently, the traditional anti-protein adhesion mechanism involves increasing the hydrophilicity of the material surface. For example, Bing Xia et al. grafted biocompatible polyethylene glycol (PEG) onto the surface of ultra-high molecular weight polyethylene (UHMWPE) using UV initiation, achieving effective antifouling effects against three model proteins, including bovine serum albumin, lysozyme, and fibrinogen. Xiang Tao et al. prepared an ion strength-sensitive membrane with good antifouling properties and blood compatibility by in-situ crosslinking polymerization of sulfomethacrylate (SBMA) in polyethersulfone (PES) solution. The antifouling mechanism of hydrophilic materials relies on the hydration layer on the material surface. However, when the interaction strength between the membrane surface and contaminants is greater than the interaction strength between the membrane surface and the aqueous medium, the hydration layer may be breached or replaced. This explains why hydrophilic surfaces are more difficult to clean than hydrophobic surfaces. Furthermore, since ECMO membranes operate at the gas-liquid interface, improper hydrophilic modification may lead to liquid leakage. Therefore, new approaches are needed for ECMO membranes. Summary of the Invention

[0004] To address the aforementioned shortcomings, this invention introduces the concept of hydrophilic-low surface energy into ECMO, preparing a modified polyethersulfone membrane with a single-sided coating possessing antifouling capabilities and blood compatibility. This is achieved by introducing amino groups into the polyethyleneimine coating through adhesion of tannic acid and ferric iron; then, fluorine-containing small molecules are grafted via a ring-opening reaction of amino and epoxy groups, thus constructing a hydrophilic-low surface energy antifouling membrane. Simultaneously, the resulting modified membrane exhibits excellent blood compatibility, ensuring stability under long-term operation. Therefore, it was used for gas separation in ECMO. In simulated ECMO experiments, the results confirmed that the obtained modified polyethersulfone membrane displayed excellent oxygenation and carbon dioxide removal efficiency, with no plasma leakage. Therefore, this invention provides a simple and easy-to-implement industrial method for preparing PES oxygenation membranes, possessing significant application potential.

[0005] The technical solution of the present invention:

[0006] The first technical problem to be solved by the present invention is to provide a method for preparing a hydrophilic, low surface energy modified polyethersulfone film. The preparation method is as follows: first, the polyethersulfone film is hydrophilically modified to obtain a polyethersulfone film with a hydrophilic coating; then, the modified polyethersulfone film is hydrophobically modified on the polyethersulfone film with the hydrophilic coating to obtain the modified polyethersulfone film. In this case, 3-perfluorobutyl-1,2-epoxypropane (2,2,3,3,4,4,5,5,5-nonafluoropentylepoxyethylene) is used for hydrophobic modification.

[0007] Furthermore, the method for hydrophobically modifying the obtained polyethersulfone film with a hydrophilic coating is as follows: the obtained polyethersulfone film with a hydrophilic coating is placed in a 3-perfluorobutyl-1,2-epoxypropane (NFO) solution and allowed to stand at 45-60°C (preferably 50°C) for 12-18 hours (preferably 15 hours), and then washed and dried to obtain the modified polyethersulfone film.

[0008] Furthermore, the 3-perfluorobutyl-1,2-epoxypropane solution is a solution prepared by mixing 3-perfluorobutyl-1,2-epoxypropane with a solvent at a volume ratio of 175 μL to 360 μL: 10 mL, wherein the solvent is at least one of water, ethanol, or dimethyl sulfoxide.

[0009] Furthermore, the polyethersulfone membrane with the hydrophilic coating is prepared by the following method: the polyethersulfone membrane (PES membrane) is allowed to stand in tannic acid (TA) solution and FeCl3 solution in sequence, and then the membrane is taken out and washed; then it is immersed in PBS buffer containing polyethyleneimine (PEI) and stirred overnight; finally, the obtained membrane is rinsed with deionized water to obtain the polyethersulfone membrane with the hydrophilic coating.

[0010] Furthermore, the concentration of the tannic acid solution is 0.8–1.2 mg / ml (preferably 1 mg / ml), and the concentration of the FeCl3 solution is 0.3–0.8 mg / ml (preferably 0.5 mg / ml).

[0011] Furthermore, the PEI concentration in the PBS buffer containing polyethyleneimine is 5–20 mg / ml (preferably 10 mg / ml).

[0012] Furthermore, the pH of the PBS buffer containing polyethyleneimine is 7.2 to 8.5 (preferably 8.5).

[0013] The second technical problem to be solved by the present invention is to provide a hydrophilic, low surface energy modified polyethersulfone film, which is prepared by the above method.

[0014] The third technical problem to be solved by the present invention is to point out that the above-mentioned hydrophilic low surface energy modified polyethersulfone membrane can be used as an antifouling membrane, a separation membrane or an ECMO membrane.

[0015] The fourth technical problem to be solved by the present invention is to provide an ECMO membrane, wherein the membrane is a hydrophilic low surface energy modified polyethersulfone membrane, which is prepared by the following method: firstly, the polyethersulfone membrane is hydrophilically modified to obtain a polyethersulfone membrane with a hydrophilic coating; then, the modified polyethersulfone membrane is hydrophobically modified on the polyethersulfone membrane with the hydrophilic coating to obtain the modified polyethersulfone membrane, wherein 3-perfluorobutyl-1,2-epoxypropane (2,2,3,3,4,4,5,5,5-nonafluoropentylepoxyethylene) is used for hydrophobic modification.

[0016] The beneficial effects of this invention are:

[0017] This invention introduces a "hydrophilic-low surface energy" mechanism into ECMO. For example, it utilizes tannic acid grafted with PEI to form a hydrophilic substrate, ensuring contaminant resistance. Then, it grafts small molecules containing short-chain fluorine through a ring-opening reaction of amino and epoxy groups, introducing a low surface energy portion to ensure contaminant release performance. Simultaneously, the resulting modified PES membrane exhibits excellent blood compatibility. Therefore, it can be used as a membrane oxygenator in ECMO. In simulated ECMO tests, the modified membrane demonstrated excellent gas exchange performance and anti-plasma leakage performance. Furthermore, the preparation method of the modified membrane of this invention is simple, has a wide range of applications, and possesses significant application potential. Attached Figure Description

[0018] Figure 1 (A) Flowchart and (B) Mechanism diagram of the preparation of M-TA / PEI-NFO.

[0019] Figure 2(A) XPS full spectrum of M-PES, M-TA / PEI, and M-TA / PEI-NFO; (B) C1s micro-spectrum of M-TA / PEI-NFO; (C) F1s micro-spectrum of M-TA / PEI-NFO.

[0020] Figure 3 (A) Surface SEM images of M-PES, M-TA / PEI, and M-TA / PEI-NFO; (B) two-dimensional and (C) three-dimensional AFM images of the surfaces of M-PES, M-TA / PEI, and M-TA / PEI-NFO.

[0021] Figure 4 (A) Graph of static water contact angle of membrane and (B) Zeta potential graph, (C) Graph of static water contact angle of membrane as a function of concentration; ** indicates significant difference P value < 0.01; **** indicates significant difference P value < 0.0001; "ns" indicates no significant difference (P>0.05).

[0022] Figure 5 (A) Graph showing the adhesion of BSA proteins on the membrane surface as detected by the BCA protein kit; (B) Graph showing the change of the third harmonic frequency curve of the QCM-D sensor coated with M-PES, M-TA / PEI and M-TA / PEI-NFO over time in BSA protein solution; (C) Graph showing the adsorption of proteins on the surface of the QCM chip on M-TA / PEI-NFO, M-PES and M-TA / PEI before and after PBS rinsing.

[0023] Figure 6 (A) Blood cell count diagram of white blood cells, red blood cells and platelets; (B) Hemolysis rate diagram of M-PES, M-TA / PEI, and M-TA / PEI-NFO; (C) Attachment of red blood cells and (D) Platelets on the surface of M-PES, M-TA / PEI, and M-TA / PEI-NFO; Concentration of (E)PF4, (F)C3a and (G)C5a in plasma after culture with different membranes; "ns" indicates no significant difference (P>0.05).

[0024] Figure 7 (A) Gas permeation test results of M-PES, M-TA / PEI, and M-TA / PEI-NFO; (B) Comparison of CO2 and O2 permeability of different membranes; (C) Schematic diagram of constant volume pressure swing gas permeation test method; (D) Residual carbon dioxide concentration after circulation in carbon dioxide removal test; (E) Oxygenation curves of M-PES, M-TA / PEI, and M-TA / PEI-NFO; (F) Relative humidity change of M-TA / PEI-NFO with temperature change in plasma leakage experiment; The effective membrane area of ​​ECMO simulation test is 12.56 square centimeters. Detailed Implementation

[0025] This invention introduces a hydrophilic-low surface energy approach into ECMO to prepare an antifouling-release membrane. ECMO membranes suffer from blood compatibility issues during use, and protein adsorption is the first interaction between blood and the material, leading to compatibility problems and decreased permeability. This invention first grafts polyethyleneimine with tannic acid onto a PES membrane to form a hydrophilic coating (TA / PEI coating), creating a hydration layer to prevent contaminant diffusion. Then, a low-surface-energy fluorinated small molecule (NFO, a short-chain fluorocarbon molecule containing epoxy groups) is grafted via a ring-opening reaction. The grafted NFO, acting as a low-surface-energy component, ensures its fouling release performance. This results in a fouling-release membrane with a hydrophilic continuous phase and a low-surface-energy dispersed phase. The hydrophilic substrate resists fouling adhesion by forming a hydration layer, while the low-surface-energy hydrophobic portion ensures fouling release performance. The membrane's anti-protein adhesion performance was then assessed using a BCA kit and a quartz crystal microbalance (QCM-D). Blood routine tests, erythrocyte and platelet adhesion assays, and ELISA experiments demonstrated that the synthesized membrane exhibits good blood compatibility. Finally, a simulated ECMO cycle test was conducted, demonstrating that the synthesized membrane possesses excellent gas exchange performance and resistance to plasma leakage. This invention is the first to introduce a hydrophilic-low surface energy system into ECMO; furthermore, the surface coating method enhances the membrane's antifouling ability without damaging the bulk structure.

[0026] The specific embodiments of the present invention will be further described below with reference to examples, but the present invention is not limited to the scope of the examples described.

[0027] Raw materials: Polyethersulfone (PES) was purchased from BASF AG, Germany; tannic acid (TA, ACS grade); ferric chloride hexahydrate (FeCl3·6H2O, 99%, analytical grade); polyethyleneimine (PEI, weight average molecular weight 10,000, 99%); 3-perfluorobutyl-1,2-epoxypropane (chromatographic grade, >98%); bovine serum albumin (BSA, New Zealand source, purified grade, ≥98.0%); and sodium dodecyl sulfate (SDS, analytical grade, 92.5-100.5%) were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; N,N-dimethylacetamide (DMAc, analytical grade, ≥99.0%) and anhydrous ethanol (analytical grade, ≥99.7%) were purchased from Chengdu Kelon Chemical Co., Ltd. BCA protein concentration kit and fibrinogen (BFG, 93%) were purchased from Beijing Solarbio Science & Technology Co., Ltd. Human complement fragment 3a (C3a) kit, human complement fragment 5a (C5a) kit, and human platelet factor 4 kit were purchased from China Cusabbio Biotechnology Co., Ltd. All chemicals were used immediately upon receipt.

[0028] Example 1

[0029] like Figure 1 The self-made polyethersulfone membrane shown was prepared by phase inversion method: water was used as a non-solvent, 18g of PES particles were added to 82g of DMAC, and mechanically stirred at 80 degrees for 4h. Then, the membrane was degassed at room temperature in a vacuum oven, and prepared by spin coating. The PES-coated glass plate was then immersed in water and repeatedly soaked in water to remove impurities, resulting in a PES membrane (denoted as M-PES).

[0030] The prepared M-PES membrane was added to a 1 mg / ml TA solution and gently shaken for 10 min. Then it was added to a 0.5 mg / ml FeCl3 solution and gently shaken for 5 min. The membrane was then removed and rinsed thoroughly with deionized water several times. It was then immersed in a PBS buffer solution with a PEI concentration of 10 mg / ml (pH = 8.5) overnight with shaking. Finally, the membrane was rinsed thoroughly with deionized water to obtain a polyethersulfone membrane (M-TA / PEI) with a hydrophilic coating.

[0031] The polyethersulfone membrane with hydrophilic coating obtained in the previous step was immersed in 50 ml of ethanol solution, and 890 μL of NFO was added. The reaction was carried out at 50 degrees Celsius for 15 h. The membrane was then rinsed with ethanol and water to obtain the modified PES membrane of the present invention. The membrane was named M-TA / PEI-NFO, also known as NFO-100 (indicating that the concentration of NFO is 100 mmol / L).

[0032] Example 2

[0033] The other preparation process is the same as in Example 1, except that 1335.75 μL of NFO is added, and the resulting modified PES membrane is designated as NFO-150.

[0034] Example 3

[0035] The other preparation process is the same as in Example 1, except that 1781 μL of NFO is added, and the resulting modified PES membrane is designated as NFO-200.

[0036] Comparative Example 1

[0037] The other preparation process is the same as in Example 1, except that 44.53 μL of NFO is added, and the resulting modified PES membrane is designated as NFO-5.

[0038] Comparative Example 2

[0039] The other preparation process is the same as in Example 1, except that 89.05 μL of NFO is added, and the resulting modified PES membrane is designated as NFO-10.

[0040] Comparative Example 3

[0041] The other preparation process is the same as in Example 1, except that 222.63 μL of NFO is added, and the resulting modified PES membrane is designated as NFO-25.

[0042] Comparative Example 4

[0043] The other preparation process is the same as in Example 1, except that 445.25 μL of NFO is added, and the resulting modified PES membrane is designated as NFO-50.

[0044] Comparative Example 5

[0045] The other preparation process is the same as in Example 1, except that 667.88 μL of NFO is added, and the resulting modified PES membrane is designated as NFO-75.

[0046] Performance testing:

[0047] The surface morphology and roughness of the membrane were characterized using scanning electron microscopy (SEM, Apreo S HiVoc, American) and atomic force microscopy (AFM, Icon, American). The chemical structure and specific valence states of the membrane were analyzed using XPS. The hydrophilicity / hydrophobicity and charge carrying capacity of the membrane surface were characterized using water contact angle (WCA) and membrane zeta potential. The selectivity of functional groups for CO2 was determined using BET (ASAP2020, Micromeritics, America) through CO2 gas adsorption.

[0048] The BSA content adhering to the membrane surface was qualitatively represented by laser confocal microscopy. A 1*1 cm membrane was incubated at 37°C in the dark for 3 hours using 0.1 mg / ml FTIC-BSA (PBS solution), rinsed with PBS, and then stored immersed in PBS. The BSA adhesion of the membrane was characterized using laser confocal microscopy.

[0049] The content of BSA protein adhering to the membrane surface was quantitatively determined using the BCA kit method. Membranes were cut into 1*1cm pieces and placed in 24-well plates. The pieces were pre-soaked in PBS buffer overnight, and on the day of testing, incubated at 37°C for 1 hour before removing the PBS. Then, 1 ml of 1 mg / ml BSA solution was added to each sample, and the plate was incubated at 37°C for 1 hour. The membranes were then gently washed three times in PBS and three times in water using tweezers. After rinsing, the membranes were added to the wells, and 0.2 ml of SDS solution was added to each well. The plates were then incubated at 37°C with vigorous shaking for 1 hour. The protein content adhering to the membrane surface was determined using a standard curve prepared with the kit.

[0050] The adhesion and separation of BSA and BFG on the membrane surface were characterized using QCM-D. A 2% PES film-forming solution was spin-coated onto a gold-coated quartz chip, prepared using the same method as described above. The chip was spin-coated at 4000 rpm for 100 s, and then TAPIEI and NFO were coated onto the PES-coated chip using the same method described above, resulting in PES-coated, TAPIEI-coated, and NFO-coated chips, respectively. Finally, the sensor was placed at room temperature for 4 hours until the solvent completely evaporated, forming a dry polymer film. The three chips were then placed in the QCM-D channel and tested at a pump rate of 100 μL / min. Before each measurement, the chip was rinsed with Milli-Q water to obtain a stable baseline. A signal was considered stable when the frequency change was less than ±1 Hz within 10 minutes. This invention uses QCM-D to detect the change in the resonant frequency (Δf) of the chip at several harmonics (1st, 3rd, 5th, and 7th harmonics) and calculates the mass change of the chip surface before and after PBS rinsing using a viscoelastic model.

[0051] Complete blood count (CBC): The effect of the membrane on blood cells is characterized by a CBC. The membrane is co-incubated with EDTA-anticoagulated whole blood, and then the CBC analyzer is used for characterization.

[0052] Hemolysis and erythrocyte adhesion: The hemolysis experiment was used to reflect the effect of the membrane on erythrocytes. A 1*1 cm membrane was co-incubated with centrifuged erythrocytes at 37°C for 1 hour, and the hemolysis rate was then detected by ELISA reader, with comparisons to negative and positive samples. Furthermore, the morphology of erythrocytes fixed on the membrane surface after co-incubation was observed by SEM to further reflect the effect of the membrane on erythrocyte morphology.

[0053] Platelet adhesion: Platelet adhesion experiments are used to reflect the adhesion and activation behavior of platelets on the membrane. Centrifuged platelets (PRPs) are co-incubated with the membrane and then fixed. Platelets on the membrane surface are observed using SEM.

[0054] ELISA (Enzyme-Linked Immunosorbent Assay): This invention detects complement and contact activation levels in membranes using a commercially available enzyme-linked immunosorbent assay (ELISA). The invention utilizes C3a, C5a, and platelet factor 4 (PF4) kits.

[0055] Carbon dioxide and oxygen permeability: The gas permeability of the membrane was determined using the differential pressure method. The three types of membranes were installed in the three test chambers of the device and tested simultaneously. The pre-treated sample was placed between the upper and lower test chambers and clamped. First, the low-pressure chamber (lower chamber) was evacuated, and then the entire system was evacuated. When the specified vacuum level was reached, the lower test chamber was closed, and a certain pressure of test gas was introduced into the high-pressure chamber (upper chamber), ensuring a constant (adjustable) pressure difference across the sample. In this way, the gas would permeate from the high-pressure side to the low-pressure side under the action of the pressure gradient. By monitoring and analyzing the pressure in the low-pressure side, the various barrier parameters of the tested sample were obtained.

[0056] Membrane performance in a simulated ECMO device: To evaluate the actual performance of the membranes, this invention employs a gas-liquid circulation test device to realistically simulate the membrane's actual working environment. The oxygenation and carbon dioxide removal performance of three different membranes were tested sequentially using this device. A saturated carbon dioxide solution was circulated in the upper chamber of the device, while a stream of pure oxygen was introduced into the lower chamber. A dissolved oxygen meter probe was fixed in the solution pool, and the oxygen concentration in the solution was measured every five minutes using a dissolved oxygen meter. The experiment was conducted in a completely closed system. The test lasted for one hour, and after the test, a liquid carbon dioxide detector was used to measure the remaining carbon dioxide content in the circulated solution.

[0057] To investigate plasma leakage of the membrane in actual use, under simulated conditions, this invention circulated lecithin solution (1.5g L-α-lecithin dissolved in 500ml physiological saline) in the upper chamber of the device, while oxygen was blown out along the other surface of the membrane in the lower chamber, maintaining a liquid-to-liquid ratio of 1:2.5. The purge gas outlet led to a sealed three-necked flask equipped with a humidity detector. The changes in the humidity detector readings were recorded.

[0058] Meanwhile, to further simulate the usage conditions in a real environment, this invention used pig blood with added anticoagulant to replace deionized water and conducted the above tests.

[0059] Results and Discussion

[0060] 1. Chemical and physical structural characterization of the membrane

[0061] First, XPS was used to characterize the elemental composition of the three films, such as Figure 2As shown in Figure A, the M-TA / PEI obtained in this invention, compared with M-PES, has an additional N1s peak of 399.2 eV, indicating the successful introduction of PEI. M-TA / PEI-NFO also has an additional F1s peak of 688.3 eV, indicating the successful grafting of the NFO monomer. Furthermore, the elemental content on the membrane is also shown in Table 1. Compared with M-PES, M-TA / PEI adds N element, with a content of 18.02%, indicating the presence of PEI on the membrane surface. F element was detected in M-TA / PEI-NFO, with a content of 6.37%. In addition, Figure 2 B and Figure 2 C1S and F1S microspectral data for M-TA / PEI-NFO were displayed. The C1S microspectral data showed five peaks at binding energies of 284.8 eV, 285.7 eV, 287.5 eV, 291.2 eV, and 293.6 eV, corresponding to CC, CN(CO), C=O, CF2, and CF3, respectively. The F1S microspectral data showed peaks at 683.9 eV and 688.4 eV, corresponding to CF3 and CF2, respectively. XPS analysis confirmed that NFO was successfully grafted onto the TA / PEI coated PES film.

[0062] Table 1. Elemental composition of the membrane surface analyzed by XPS

[0063]

[0064] The surface of the membrane is characterized by SEM, such as Figure 3 As shown in the SEM images in Figure A, the surface of M-PES is relatively smooth, with obvious pores. However, after grafting NFO molecules, the pore size decreases, which will help reduce plasma leakage. Furthermore, the microstructure of the membrane surface was further investigated using AFM, such as... Figure 3 As shown in B and 3C, M-TA / PES has the roughest surface, mainly due to the uneven particle size on the membrane. However, after grafting NFO, the surface roughness decreases, a characteristic that will benefit its antifouling performance.

[0065] 2. Water contact angle of membrane surface

[0066] The water contact angle of a membrane surface reflects changes in its hydrophilicity or hydrophobicity, and plays a crucial role in the surface's biocompatibility and antifouling ability. The water contact angle of the membrane obtained in Example 1 of this invention is as follows: Figure 4 As shown in Figure A, the water contact angle (WCA) of M-PES is approximately 70.5 degrees, due to the hydrophobicity of polyethersulfone. For M-TA / PEI, the WCA decreases to around 43.7 degrees due to the introduction of numerous phenolic hydroxyl groups in TA and amino groups in PEI. Then, after grafting low surface energy NFO molecules, the material surface becomes hydrophobic again, and the WCA reaches 89.6 degrees.

[0067] Figure 4 (C) shows the change in water contact angle of NFO membranes with different concentrations (mmol / L). After grafting TA / PEI onto PES, the water contact angle decreases because the coating is hydrophilic. After grafting with low surface energy NFO, the water contact angle should increase. However, when the present invention grafts low concentration NFO, the water contact angle decreases instead. Only when the NFO concentration reaches 75% does the water contact angle show a significant change. Only when the NFO concentration reaches 100% does it have a hydrophobic effect. Only with a certain degree of hydrophobicity can the membrane obtained by the present invention have an advantage in subsequent gas-liquid exchange (hydrophobic membranes are beneficial for gas-liquid exchange).

[0068] 3. Zete potential on the film surface

[0069] like Figure 4 As shown in Figure B, the Zeta potential of M-PES is around -29.7 mV. After the polyethyleneimine coating, the Zeta potential on the membrane surface rises to around +6.9 mV, because PEI is a typical positive polyelectrolyte. However, after grafting NFO, the Zeta potential on the membrane surface drops to around -7.1 mV. This may be because F is an electronegative group, and the grafting of epoxy groups also consumes some amine groups. Higher surface charge usually leads to greater electrostatic interactions between contaminants and the membrane surface, thus exacerbating membrane fouling. Therefore, reducing the Zeta potential is beneficial for improving the membrane's antifouling ability.

[0070] 4. Antifouling properties of the membrane surface

[0071] It is generally believed that the denaturation of adsorbed proteins can initiate coagulation activation and immune inflammatory responses. Furthermore, in the clinical use of ECMO, the adhesion of blood proteins and blood cells to the surface leads to membrane blockage, covering and clogging membrane pores, hindering gas exchange (oxygen transport and carbon dioxide removal), and causing a rapid decline in the oxygenator's efficiency. Therefore, avoiding and controlling protein adsorption can significantly improve the blood compatibility and gas exchange efficiency of current membrane materials. In view of this, this invention investigates the in vitro adsorption of BSA and BFG on three types of membranes.

[0072] like Figure 5 As shown in Figure A, the M-PES surface exhibits the highest BSA adhesion. Although BSA is negatively charged at neutral pH, the adhesion amount on the M-TA / PEI surface is relatively reduced compared to M-PES. This may be because the Zeta potential shows that the positive charge of M-TA / PEI is not high, and the PEI surface is highly hydrophilic. However, after grafting NFO, the surface anti-BSA adhesion effect significantly increased.

[0073] Subsequently, the dynamic adhesion of proteins to the membrane surface was further investigated using a quartz crystal microbalance (QCM-D). When the polymer membrane was exposed to BSA solution, the third harmonic distortion (HHD) showed a sharp decrease within the first few minutes of contact, while the rate of decrease slowed down after 800 seconds. This indicates that after sudden exposure to BSA solution, the surface mass of the polymer membrane significantly increased, and proteins rapidly accumulated on the polymer membrane before gradually stabilizing. Figure 5 As shown in Figure B, the amount of BSA adhering to the M-TA / PEI-NFO surface is significantly less than that of M-TA / PEI and M-PES, indicating that the antifouling ability of the membrane surface is improved after the introduction of the "hydrophilic-low surface energy" mechanism. Since the adsorption of BSA on the membrane can be considered a dynamic process, some BSA may be loosely adsorbed on the membrane in solutions with high BSA content. To detect the fouling release characteristics of these membranes, after culturing in a BSA solution for 1 hour, the surface was rinsed with PBS to remove loosely bound BSA. The results showed that the third harmonic frequency of the crystal in both the bare sensor and the polymer brush membrane increased significantly, proving that BSA had been released from the surface.

[0074] To further quantify the amount of surface BSA before and after PBS rinsing, this invention uses the Voigt viscoelastic model to calculate the mass of surface BSA. Figure 5 C). After 1 hour of exposure to BSA solution, the mass of BSA adhering to the surfaces of the three membranes were 1194.7, 974.9, and 663.9 ng / cm³, respectively. 2 After rinsing with PBS buffer, these values ​​decreased to 1031.2, 801.4, and 483.9 ng / cm³, respectively. 2 The removal rates reached 13.7%, 17.8%, and 27.1%, respectively. The removal rate over 15 minutes also demonstrates that M-TA / PEI-NFO exhibits good fouling release performance.

[0075] These results validate the improved ability of the modified membrane to resist protein adhesion, which is mainly due to the synergistic effect of the hydrophilic and hydrophobic water regions on the membrane surface, reducing the interfacial interaction between the surface and pollutants.

[0076] 5. Membrane blood compatibility

[0077] Membrane oxygenators act as a barrier for blood-gas exchange; therefore, assessing blood compatibility is crucial for ECMO membranes. Other blood compatibility tests were conducted here. First, a complete blood count was performed to investigate the effect of the membrane obtained in this invention on blood cells. For example... Figure 6As shown in Figure A, the number of WBCs, RBCs, and PLTs in the blood treated with M-TA / PEI-NFO is almost identical to the number of blood cells in the control sample, indicating that the modified membrane obtained in this invention has no serious effect on blood cells.

[0078] Then, this invention investigates whether the modified membrane poses a risk of erythrocyte lysis upon contact with erythrocytes through a hemolysis experiment. If the hemolysis rate of the material is less than 5%, it meets the hemolysis test requirements for medical materials. Figure 6 As shown in Figure B, the hemolysis rates of both M-PES and M-TA / PEI-NFO were less than 5%, meeting the requirements for use as medical materials. No significant color change was observed in the co-incubation solution after centrifugation. Furthermore, this invention fixes the erythrocytes on the membrane surface after co-incubation, and the number and morphology of the erythrocytes adhering to the membrane surface are observed using SEM. Figure 6 As shown in Figure C, the M-PES and M-TA / PEI membranes have a higher number of adhering red blood cells, most of which are deformed or ruptured. In contrast, the M-TA / PEI-NFO membrane has a lower number of adhering red blood cells, and almost all of them are biconcave discs. This indicates that the modified membrane obtained in this invention has good compatibility with red blood cells.

[0079] Platelet adhesion and activation are considered key events in thrombosis and are widely used in assessing the blood compatibility of materials. When platelets are activated, they extend prominent pseudopodia. For example... Figure 6 As shown in Figure D, most platelets adhering to the surfaces of M-PES and M-TA / PEI membranes were activated. However, no obvious pseudopodia extension was observed on the M-TA / PEI-NFO surface, indicating that our modified membrane did not activate platelets.

[0080] Further investigation into the interaction between blood and materials was conducted through ELISA experiments. Figure 6 At E and 6F, no significant complement activation was observed in M-TA / PEI and M-TA / PEI-NFO compared to the control sample, while showing better improvement compared to M-PES. M-TA / PEI-NFO also did not significantly change PF4 concentration. Figure 6 G) also proved that there was no obvious platelet activation phenomenon, which is consistent with the platelet morphology observed on SEM in this invention.

[0081] 6. Gas permeability

[0082] To further verify the influence of the coating on the gas permeation performance of the membrane, this invention systematically analyzed the gas transport characteristics of the membrane using the differential pressure method. For example... Figure 7As shown in Figure A, due to the coating blocking some of the membrane pores, the oxygen and carbon dioxide permeability of M-TA / PEI and M-TA / PEI-NFO decreased slightly, but there was no substantial impact. The oxygen and carbon dioxide permeability of M-TA / PEI-NFO reached 467.6 Barrer (a unit used to assess gas permeability) and 449.9 Barrer, respectively.

[0083] Simultaneously, the permeability data of the membrane obtained by this invention are compared with those of other relevant ECMO membranes, such as... Figure 7 As shown in B, although the CO2 and O2 permeability of the present invention is still lower than that of the 3M Oxyplus membrane, a currently available commercial oxygenation membrane resource, it has surpassed that of most of the currently studied membrane oxygenation membranes.

[0084] 7. Performance under simulated ECMO device

[0085] In the clinical application of ECMO, the membrane acts as a barrier between blood and gases, preventing direct contact between them. To simulate the actual performance of the membrane as closely as possible, this invention employs... Figure 7 The gas-liquid circulation device shown in C was used to study the gas exchange and plasma leakage prevention performance of the membrane.

[0086] like Figure 7 As shown in Figure D, in the gas exchange experiment, the carbon dioxide content in the liquid after circulation was detected using a liquid carbon dioxide detector. After 60 minutes of circulation, the carbon dioxide concentration of M-TA / PEI-NFO showed a more significant decrease compared to the other two membranes. Simultaneously, in the oxygenation experiment, the growth rate and final oxygen content of M-TA / PEI-NFO showed a significant advantage over the other two membranes. Figure 7 E), the final oxygen concentrations in the liquid after the three membrane cycles were 7.07, 6.63 and 7.78 mg / L, respectively.

[0087] This seems to contradict the gas permeation parameters obtained by the pressure difference method, but this is because the two tests are conducted in different environments. Unlike the gas-gas environment tested by the pressure difference method, this invention uses a gas-liquid circulation device to simulate the gas-liquid interface in the working environment of the ECMO membrane. In this environment, the hydrophobic properties of M-TA / PEI-NFO are effectively demonstrated. Gas will accumulate at the interface of the hydrophobic membrane. At the same time, due to the high carbon dioxide content in the liquid and the continuous gas flow on the other side of the membrane, carbon dioxide is removed quickly.

[0088] Plasma leakage has always been a serious problem for membrane oxygenators (MEAs). During ECMO cycles, plasma may enter the gas flow through the membrane pores, leading to a decrease in gas exchange efficiency and inevitably requiring replacement of the oxygenator. Therefore, this invention uses a gas-liquid circulation device to simulate this test. The humidity change of the oxygen flow under the action of the modified membrane is continuously monitored using a humidity detector, such as... Figure 7 As shown in Figure F, during the 96-hour continuous cycle, the relative humidity and temperature fluctuated slightly but did not change significantly, and they changed almost synchronously with opposite trends, indicating that the humidity in the outlet airflow remained almost constant. Furthermore, when this device was connected to anhydrous copper sulfate, no color change was observed after 7 days of operation, demonstrating that the modified membrane of this invention possesses excellent anti-plasma leakage properties. During ECMO treatment, the membrane comes into contact with blood, not water; therefore, the modified membrane obtained by this invention has good anti-plasma leakage capability.

Claims

1. A method for preparing a hydrophilic, low surface energy modified polyethersulfone film, characterized in that, The preparation method is as follows: First, a polyethersulfone (PES) membrane is hydrophilically modified to obtain a PES membrane with a hydrophilic coating; then, the PES membrane with the hydrophilic coating is hydrophobically modified to obtain the modified PES membrane, wherein 3-perfluorobutyl-1,2-epoxypropane is used for hydrophobic modification; the PES membrane with the hydrophilic coating is prepared by the following method: the PES membrane is allowed to stand in tannic acid solution and FeCl3 solution sequentially, then the membrane is taken out and washed; then it is immersed in PBS buffer containing polyethyleneimine and stirred overnight; finally... The obtained membrane was then rinsed with deionized water to obtain the polyethersulfone membrane with the hydrophilic coating. The method for hydrophobic modification of the obtained polyethersulfone membrane with the hydrophilic coating is as follows: the obtained polyethersulfone membrane with the hydrophilic coating is placed in a 3-perfluorobutyl-1,2-epoxypropane solution and allowed to stand at 45-60°C for 12-18 hours, and then washed and dried to obtain the modified polyethersulfone membrane. The 3-perfluorobutyl-1,2-epoxypropane solution is a solution prepared by mixing 3-perfluorobutyl-1,2-epoxypropane with a solvent at a volume ratio of 175µL-360µL:10mL, wherein the solvent is at least one of water, ethanol or dimethyl sulfoxide.

2. The method for preparing a hydrophilic, low surface energy modified polyethersulfone film according to claim 1, characterized in that, The concentration of the tannic acid solution is 0.8–1.2 mg / ml, and the concentration of the FeCl3 solution is 0.3–0.8 mg / ml.

3. The method for preparing a hydrophilic, low surface energy modified polyethersulfone film according to claim 1, characterized in that, The PBS buffer containing polyethyleneimine has a PEI concentration of 5–20 mg / ml.

4. The method for preparing a hydrophilic, low surface energy modified polyethersulfone film according to claim 1, characterized in that, The pH of the PBS buffer containing polyethyleneimine is 7.2–8.

5.

5. A hydrophilic, low surface energy modified polyethersulfone film, characterized in that, The modified polyethersulfone film is prepared by any one of claims 1 to 4.

6. The hydrophilic, low surface energy modified polyethersulfone membrane prepared by any one of claims 1 to 4 may be used as an antifouling membrane, a separation membrane, or an ECMO membrane.

7. An ECMO membrane, characterized in that, The membrane is a hydrophilic, low surface energy modified polyethersulfone membrane as described in claim 5, which is prepared by the following method: first, the polyethersulfone membrane is hydrophilically modified to obtain a polyethersulfone membrane with a hydrophilic coating; then, the modified polyethersulfone membrane is hydrophobically modified on the polyethersulfone membrane with the hydrophilic coating to obtain the modified polyethersulfone membrane, wherein 3-perfluorobutyl-1,2-epoxypropane is used for hydrophobic modification.

Citation Information

Patent Citations

  • Catalytic membrane, preparation method and application thereof

    CN111330463A

  • Production of microporous polysulfone hollow-fiber membrane, useful for membrane oxygenation of blood, involves coating gas side of membrane with hydrophobic material

    DE10034098A1

  • Composite semipermeable membrane

    JP2020138135A